"Inherited Gentrification": Changing Profiles of Gentrifiers via Inheritance, The Case of Bozcaada - Okumuş, Duygu (Konya Technical Univ, Fac Architecture & Design, 2020)
Purpose Rural areas have been through structural changes. The reorganisation of the rural economy from agriculture to services, in addition to improvements in transportation and infrastructures, migration patterns have started to reverse in some regions and hence to change the social composition of those regions' rural areas. These changes and their implications have been largely debated in the rural gentrification literature, mainly by re-presenting cases from the Anglo-Saxon world. This paper contributes to the rural gentrification literature by presenting an empirical study on a socio-cultural and demographic change that, together with a local economic shift, is taking place in a location other than the Global North. Design/Methodology/Approach A qualitative case study examining the changes on the socio-spatial structure of a small Turkish island, Bozcaada, is presented through the following principal indicators of countryside gentrification: the change in the socio-economic composition of its citizens; the emphasis on cultural or national heritage and aesthetics; the emergence of new institutions leading to the closure of older ones; the diversification of products and services; and the change in properties' value. Findings The first-generation newcomers were in line with the typical gentrifier's profile of rural gentrification studies. Differently, the second-generation newcomers have shown diversity in terms of both motivation and socio-economic class. This study argues that the second-generation newcomers took part naturally in the gentrification process not because they inherited their parents' properties, but also they play an important role in the significant socio-economic and cultural changes that are still taking place on the island. Research Limitations/Implications The fact that the research is based on a single case study is a limitation for its generalisation. However, the case examined provides a basis for future work that may validate its findings in different contexts. Originality/Value This paper contributes to the rural gentrification literature by introducing a new type of gentrification process, the 'inherited gentrification' with the identification of the second-generation gentrifiers of the island, who are the direct descendants of the first gentrifiers.
Keywords: Gentrification; tourism development; rural transformation; gentrifiers